ASSESSMENT OF MICROPLASTIC POLLUTION LOAD INDEX IN GISIK CEMANDI RIVER ESTUARY - Shafa Dahniar Ashara; Arseto Yekti Bagastyo; Zuhaida Mohd-Zaki; Deqi Rizkivia Radita (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Plastic waste pollution has become a serious environmental issue in Indonesia, particularly in aquatic ecosystems where plastics degrade into microplastics. This study aims to identify the abundance, characteristics, and ecological risk of microplastics in the water and sediment of the Gisik Cemandi River Estuary, Sidoarjo. Sampling was conducted at six stations during the morning and afternoon, covering surface and mid-depth layers for water, and sediment. Microplastics were extracted using the NOAA method and observed under a stereo microscope. The results showed that microplastics were present in all samples. The abundance in water reached 339 particles/L in the morning and 356 particles/L in the afternoon. The mid-depth layer contained a higher concentration of microplastics (209 particles/L) compared to the surface layer (153 particles/L). Fibers were the most dominant shape (90-92%), while black was the most frequent color (57-60%), and the dominant size ranged from 0.1 to 0.5 mm. The ecological risk assessment using the Pollution Load Index (PLI) indicated values ranging from 11.40 to 18.03 in the morning (Moderate Risk) and up to 28.98 in the afternoon (High Risk), with Station D consistently showing the highest risk levels. These findings highlight the significant influence of domestic and fishing activities on microplastic pollution in the estuary, necessitating urgent mitigation strategies.